Perancangan Aplikasi Pemetaan Lokasi Usaha Kecil Menengah (UKM) Di Kota Lubuklinggau Berbasis Goegraphic Information System (GIS) Dan Location Based Service (LBS) - Harma Oktafia Lingga Wijaya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
When researcher does research at the Office of Cooperatives, Micro, Small and Medium Enterprises in Lubuklinggau, author medapati that the Department of Cooperatives, Micro, Small, Medium and market management is one of the places that have different types of businesses located in various districts, villages especially regarding Small and Medium Enterprises (SMEs). But these efforts have not been widely known by the public. One problem is the lack of information regarding the location of the location of Small and Medium Enterprises (SMEs). Therefore, it is necessary websites using Geographic Information System (GIS) and Location Based Services (LBS), which will assist and facilitate citizens Lubuklinggau city to be able to obtain information and to know more about the city's existing SMEs Lubuklinggau. For Location Based Service (LBS) and Geographic Information System (GIS) itself uses the facilities of Google Maps to get for free. Google Maps is a free virtual globe map services and online provided by the company Google, Inc. can be found at http://maps.google.com/. Google Map offers a draggable map and satellite images and street view for the entire world and also offers a route planner and search. Google Map API is an application interface that can be accessed via Google Map Javascript that can be displayed on web pages. With this information system mapping the location of Small Business and puffed in the city Lubuklinggau this will certainly facilitate urban Lubuklinggau to seek information about the location of the location of Small and Medium Enterprises in the city Lubuklinggau for any information submitted more quickly, accurately, and efficiently.